Pondok Pesantren Berbasis Aset Wakaf di Jombang Jawa Timur - Mahrus, Moh Mahrus; Musfiroh, Imroh Atul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2021)
Waqf is no longer seen as a religious institution whose purpose, function and use is limited to the purposes of worship alone. However, it must be interpreted as a potential means to improve community welfare and fulfill the public interest, including for the world of education, especially Islamic boarding schools which are also in creating the nation's generation. This research is qualitative research by exploring information, news and opinions and explaining again regarding the role of the KH Waqf Board Foundation. Adlan Aly in the development of Islamic education. This was done, among other things, by snowball sampling interviews with several competent parties, foundation administrators, and parties who know about the ins and outs of waqf at the institution. Also by making observations. The results of this research conclude that the security of waqf assets within the KH Waqf Board Foundation. M. Adlan Aly Cukir Jombang and the Khoiriyah Hasyim Seblak Foundation Jombang. The concrete manifestation includes turning the institution (in this case initially the Putri Mu'allimat Islamic Boarding School) into a Waqf Board Foundation. The logistical consequence is that all assets belonging to the Foundation become waqf assets. In addition, there are efforts to obtain land and building certificates, both in the form of land certificates (property rights) and waqf land certificates. Likewise, with the inventoryof the Foundation's assets which is on the agenda of the Foundation's work program, at least the total assets of the Waqf Board Foundation can be known.